1973
DOI: 10.4294/jpe1952.21.125
|View full text |Cite
|
Sign up to set email alerts
|

The Quantitative Effect of Hydrostatic Confining Pressure on the Compressive Strength of Crystalline Rocks

Abstract: The effect of hydrostatic confining pressure on compressive strength of crystalline rocks is investigated in some detail on the basis of the available published experimental data.It is found that the pressure dependence of the compressive strength of rocks is same, in spite of different origins, for the same rock type and that there is no appreciable difference in the effect of confining pressure on compressive strength among diorite, diabase and peridotite, and among carbonate rocks. The quantitative relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…This value is 6.070 for the granitic rocks with m ¼4.57 and n¼0.52 [35]. This id just has a practical example as exhibited in Fig.…”
Section: Murrell Criterionmentioning
confidence: 96%
See 1 more Smart Citation
“…This value is 6.070 for the granitic rocks with m ¼4.57 and n¼0.52 [35]. This id just has a practical example as exhibited in Fig.…”
Section: Murrell Criterionmentioning
confidence: 96%
“…Mogi [34] showed that the strength data for a wide variety of rocks were expressed by the power law with an exponent close to 0.5. Ohnaka [35] showed that the scatter due to the differences in rocks and experimental conditions could be reduced if the strength and confining pressure were normalized with the UCS. For granitic rocks, for example, m¼ 4.57 and n ¼0.52.…”
Section: Murrell Criterionmentioning
confidence: 99%
“…5 have been obtained by many previous authors and discussed both empirically (e.g., OHNAKA, 1973) and theoretically (MURRELL, 1971;MOGI, 1972MOGI, , 1974. OHNAKA (1973) proposed empirically the following equation to describe the pressure dependence of the strength:…”
Section: Methodsmentioning
confidence: 99%
“…3.3 Pressure dependence of failure strength It is well known that the strength of a rock increases as confining pressure increases (MOGI, 1966OHNAKA, 1973;BYERLEE, 1967;MATSUSHIMA, 1960 b). In Fig.…”
Section: Methodsmentioning
confidence: 99%
“…K, n, α, β and γ are dimensionless. K, n of the granite and peridotite are from Ohanka [12] ; grabbro from Zang et al [5] ; basalt from Zhang et al [23] ; α, β and γ of all the columns come from this study.…”
Section: Empirical Formula Of Fracture Strength In the Lithosphere Anmentioning
confidence: 99%